Web-Based Project Monitoring Information System At PT. Fitra Wika Pekanbaru - Eddis Syah Putra Pane; Pernardi Silalahi (Yayasan Ibrahim Learning Centre Agam, 2025)
Project progress is an important indicator of the success of construction, which includes four main criteria, namely time, scope, cost, and quality. These four aspects must be monitored continuously to ensure they remain in line with the plan that was established at the outset. However, at PT. Fitra Wika Pekanbaru, the project monitoring process is still carried out manually using Microsoft Excel. This method is considered inefficient because it is prone to delays in data updates, inconsistencies in information, and difficulties in recapitulating and analyzing projects comprehensively. To overcome these problems, this study applies the Web Development Life Cycle (WDLC) method in designing and building a web-based project monitoring information system. The system was developed using the PHP programming language with a MySQL database, supported by the Bootstrap framework to produce a responsive and user-friendly interface. The result of this development is an online-based project monitoring system that not only simplifies the data input and reporting process but also enables real-time and continuous monitoring of project progress. Furthermore, this system supports management in conducting evaluations and making faster and more accurate decisions by providing comparative information between project planning and realization. Thus, the implementation of this information system is expected to improve work efficiency, reduce the risk of data loss, and support transparency and accountability in construction project management at PT. Fitra Wika Pekanbaru